ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN GALIAN DAN TIMBUNAN (STUDY KASUS : JALUR LINTAS SELATAN LOT 2 BLITAR) - Danang, Danang Wijanarko (SONDIR, 2025)
The implementation of road construction project work is always related to excavation and embankment work. This work starts with digging, eviction, moving, compacting and asphalting. If the road work has a fairly large scale of work and requires speed in carrying out the work then the road work is carried out mechanically or using heavy equipment. completion of projects on road works.The analysis used is the productivity analysis method, namely by processing data to find the productivity of the heavy equipment used, then to find out the time needed to complete the work.From the road work analysis, it was found that the volume of excavation and embankment had a total length of 2.4 km using excavator heavy equipment with a productivity of 60.43 m³/hour, a dump truck with a productivity of 23.85 m³/hour, a bulldozer with a productivity of 358,907 m³/hour, a hydraulic breaker with a productivity of 28.45 m³/hour. The total amount of excavator equipment required with a bucket capacity of 12 m³ for a dump truck with a capacity of 8 m³ is 4 dump trucks and the need for a bulldozer is 1 unit.